2016
DOI: 10.1074/jbc.m115.677799
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone-induced Acrosome Exocytosis Requires Sequential Involvement of Calcium-independent Phospholipase A2β (iPLA2β) and Group X Secreted Phospholipase A2 (sPLA2)

Abstract: Phospholipase A 2 (PLA 2 ) activity has been shown to be involved in the sperm acrosome reaction (AR), but the molecular identity of PLA 2 isoforms has remained elusive. Here, we have tested the role of two intracellular (iPLA 2 ␤ and cytosolic PLA 2 ␣) and one secreted (group X) PLA 2 s in spontaneous and progesterone (P4)-induced AR by using a set of specific inhibitors and knock-out mice. iPLA 2 ␤ is critical for spontaneous AR, whereas both iPLA 2 ␤ and group X secreted PLA 2 are involved in P4-induced AR.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 64 publications
2
31
0
Order By: Relevance
“…Progesterone is actively produced by cumulus cells after ovulation and its concentration within the cumulus matrix has not been assessed accurately. In mouse, it was recently reported that its concentration within the cumulus cells is in the micromolar range (Abi Nahed et al, 2015). In the oviductal fluid of rabbit and hamster, progesterone was found to be in the range of 2 to 100 nM depending on the phase of the estrous cycle (Libersky and Boatman, 1995; Richardson and Oliphant, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Progesterone is actively produced by cumulus cells after ovulation and its concentration within the cumulus matrix has not been assessed accurately. In mouse, it was recently reported that its concentration within the cumulus cells is in the micromolar range (Abi Nahed et al, 2015). In the oviductal fluid of rabbit and hamster, progesterone was found to be in the range of 2 to 100 nM depending on the phase of the estrous cycle (Libersky and Boatman, 1995; Richardson and Oliphant, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…In an elegant series of experiments with these inhibitors and different concentrations of progesterone, it was found that iPLA 2 β had more effect on early stages of exocytosis at lower, more physiological concentrations of 2 μM (Abi Nahed et al 2015). Later stages of exocytosis relied more on X sPLA 2 (Abi Nahed et al 2015); these results support the notion that lipid modulation is important at different stages of the regulated exocytotic event described by the acrosome exocytosis model.…”
Section: Sterol Efflux-mediated Regulation Of Sperm Phospholipidsmentioning
confidence: 76%
“…Of great interest, different isoforms seem to be responsible, suggesting possible dysfunction in specific compartments of cells undergoing spontaneous exocytosis. For example, intracellular, calcium-independent iPLA 2 β is critical for spontaneous exocytosis, whereas both it and secreted group X sPLA 2 are involved in progesteroneinduced acrosome exocytosis, to extents that differ depending on the concentration of progesterone and the kinetics of the sperm's response (Abi Nahed et al 2015).…”
Section: Sterol Efflux-mediated Regulation Of Sperm Phospholipidsmentioning
confidence: 99%
See 1 more Smart Citation
“…These inhibitors have been used to study the role of the enzyme ex vivo and in vivo and in particular in autoimmune diseases. 1922 FKGK11 showed strong reduction in the clinical severity and progression of experimental autoimmune encephalomyelitis. 19 Administration of FKGK18 to non-obese diabetic (NOD) mice significantly reduced diabetes incidence in association with reduced insulitis, improved glucose homeostasis, and β-cell preservation.…”
Section: Introductionmentioning
confidence: 98%